Standardized Unloading of Respiratory Muscles during Neurally Adjusted Ventilatory Assist: A Randomized Crossover Pilot Study. (October 2018) - Campoccia Jalde, Francesca; Jalde, Fredrik; Wallin, Mats K. E. B.; Suarez-Sipmann, Fernando; Radell, Peter J.; Nelson, David; Eksborg, Staffan; Sackey, Peter V.
Editor's Perspective: What We Already Know about This Topic: Neurally adjusted ventilatory assist matches the mechanical pressure from the ventilator to the patient's respiratory drive sensed from the electrical activity of the diaphragm, but the optimal degree of diaphragm unloading is uncertain What This Article Tells Us That Is New: This pilot study of 10 patients titrated neurally adjusted ventilatory assist to different levels of diaphragm unloading; less unloading was associated with greater diaphragm activity and improved ventilation of dependent lung Background: Currently, there is no standardized method to set the support level in neurally adjusted ventilatory assist (NAVA). The primary aim was to explore the feasibility of titrating NAVA to specific diaphragm unloading targets, based on the neuroventilatory efficiency (NVE) index. The secondary outcome was to investigate the effect of reduced diaphragm unloading on distribution of lung ventilation. Methods: This is a randomized crossover study between pressure support and NAVA at different diaphragm unloading at a single neurointensive care unit. Ten adult patients who had started weaning from mechanical ventilation completed the study. Two unloading targets were used: 40 and 60%. The NVE index was used to guide the titration of the assist in NAVA. Electrical impedance tomography data, blood-gas samples, and ventilatory parameters were collected. Results: The median unloading was 43% (interquartile range 32, 60) for 40% unloading target and 60% (interquartile range 47, 69) for 60% unloading target. NAVA with 40% unloading led to more dorsal ventilation (center of ventilation at 55% [51, 56]) compared with pressure support (52% [49, 56]; P = 0.019). No differences were found in oxygenation, CO2, and respiratory parameters. The electrical activity of the diaphragm was higher during NAVA with 40% unloading than in pressure support. Conclusions: In this pilot study, NAVA could be titrated to different diaphragm unloading levels based on the NVE index. Less unloading was associated with greater diaphragm activity and improved ventilation of the dependent lung regions. Abstract : This pilot study of 10 patients titrated neurally adjusted ventilatory assist to different levels of diaphragm unloading; less unloading was associated with greater diaphragm activity and improved ventilation of dependent lung.Supplemental Digital Content is available in the text.